Paternal Care in Collared Lemmings (Dicrostonyx richardsoni): Artifact or Adaptation? - Gajda, Anna Maria; Brooks, Ronald J. (ARCTIC, 1993)
Experiments conducted in large enclosures using 13 pairs of collared lemmings (Dicrostonyx richardsoni) and their pups examined the effects of three different treatments on paternal care. Treatments tested whether males altered their attentiveness to the pups when certainty of paternity was in question (through presence of a strange male), when alternative activities were available (through access to a running wheel), and when both factors were present simultaneously. Males covered and groomed pups equally among treatments. During the first five days of observation, males with access to a running wheel paid significantly less attention to strange males relative to males without access to a running wheel. Continuous exposure to the strange male may have been responsible for this short-term effect. Since covering and grooming of pups were unaffected by the presence of a strange male, the fathers' perceptions of their certainty of paternity were probably unaffected. Maintenance of paternal care under different conditions and in large enclosures provides further evidence that paternal care is not an artifact of laboratory conditions. Paternal care in collared lemmings may have evolved to maximize fitness of both sexes during winter.Key words: collared lemming, paternal care, winter breeding, fitness Des expériences menées dans de grands enclos, et mettant en jeu 13 couples de lemmings à collerette (Dicrostonyx richardsonii) et leurs petits, évaluaient les effets de 3 traitements différents sur les soins paternels. Ces traitements vérifiaient si les mâles modifiaient l'attention qu'ils portaient à leurs petits lorsque leur paternité était mise en doute (par la présence d'un mâle étranger), lorsque d'autres activités étaient disponibles (par l'accès à une roue d'exercice), et lorsque ces 2 facteurs étaient présents en même temps. Les mâles protégeaient leurs petits et les nettoyaient de la même façon lors des différents traitements. Au cours des 5 premiers jours d'observation, les mâles qui avaient accès à une roue ...